Salivary miRNAs as auxiliary liquid biopsy biomarkers for diagnosis in patients with oropharyngeal squamous cell carcinoma: a systematic review and meta-analysis - Nguyen, Huy; Nonaka, Taichiro (Frontiers in Genetics, 2024)
Objective: Healthcare system needs a novel approach to improve and diagnoses early oropharyngeal squamous cell carcinoma against its low survival rate. We conduct a systematic review and a comprehensive meta-analysis for the diagnostic role of blood and salivary miRNAs. Methods: Utilizing unbiased and thorough literature search in PubMed, we extracted appropriate data from qualified articles regarding different miRNAs biomarkers, method of extraction, research location, and year of publication. STATA was used to calculate sensitivity, specificity, diagnostic odds ratio, and summary receiver operating characteristic curve. Results: Included 9 studies with 399 qualified oropharyngeal squamous cell carcinoma patients yielded high diagnostic accuracy of blood miRNAs in combination with salivary miRNAs with a sensitivity of 0.70 (p < 0.001), specificity of 0.75 (p=0.26), diagnostic odds ratio of 7, and an area under the curve of 0.78. Conclusion: Combined blood-and saliva-derived miRNAs demonstrated a high diagnostic accuracy to detect oropharyngeal squamous cell carcinoma.